Beban Kerja, Komitmen Organisasional, Kepuasan Kerja Dalam Kinerja Karyawan - Indah Permatasari, Resita; Rijanti, Tristiana (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2025)
This study aims to test and analyze the effect of workload and organizational commitment as independent variables on employee performance as the dependent variable with job satisfaction as a moderating variable. This study uses quantitative research methods. The population in this study consisted of 96 employees who worked at BPKAD Pekalongan City. The technique used in collecting data is to use a survey method with a questionnaire. The data obtained from respondents were analyzed using the SPSS version 24 application. The tests used are instrument tests and model tests. Data analysis in this study used the MRA (Moderated Regression Analysis) test. The results showed that workload has a positive and significant effect on employee performance, organizational commitment has a negative and significant effect on employee performance, job satisfaction does not moderate the effect of workload on employee performance, job satisfaction moderates the effect of organizational commitment on employee performance.